Reproductive Biology and Population Dynamics of the Spadenose Shark, Scoliodon laticaudus, from the Veraval Coast, Gujarat: Implications for Fisheries Management - Makwana, Ketan; Parmar, H. L.; Ragul, Sivakumar; Solanki, D. J.; Chavda, Yashvant; Chauhan, Sweksha; Bohare, Hariom (International Journal of Bio-resource and Stress Management, 2026)
A total of 328 specimens (151 males, 177 females) were collected monthly from commercial landings from April, 2024 to March, 2025 at Veraval Fishing Harbour, Veraval coast, Gujarat, India to study the comprehensive analysis of the length-weight relationship (LWR) and reproductive biology of S. laticaudus. The spadenose shark, Scoliodon laticaudus, was a key component of elasmobranch landings in India, yet its region-specific biological data remained limited for sustainable management. The LWR revealed a negative allometric growth pattern for both sexes (pooled b=2.84, R²>0.92), consistent with findings from other Indian populations. The overall sex ratio (1:1.17 M: F) was not significantly different from 1:1, though significant monthly fluctuations were observed. Reproductive analysis indicated a seasonal cycle with peak gonadal activity (GSI) in November and March, suggesting an extended spawning period. The Hepatosomatic Index (HSI) showed a marked pre-spawning rise in females, indicating hepatic energy storage prior to reproduction, followed by a decline during peak GSI, demonstrating a clear energy trade-off. Uterine fecundity ranged from 6 to 9 embryos female-1, with a progressive increase in embryo length indicating continuous gestation. The findings confirmed that S. laticaudus in Gujarat exhibited distinct regional growth and reproductive patterns. This baseline data was crucial for developing targeted conservation and fisheries management strategies for this prolific yet vulnerable shark species.